On some properties of the linear-invariant family of n-th order - Kirjackis, Eduardas; Kirjackis, Jevgenijus (Lietuvos matematikos rinkinys, 2023)
In the work the linear-invariant family n-th order is determined. The omega-operator and the functionals related with it are introduced on this family. Their properties are studied.
Keywords: holomorphic function; omega operator; functional